ASRAMA MAHASISWA BERSUJUD TANAH BUMBU DI BANJARBARU - Noorshofiah, Noorshofiah; Wastuty, Prima Widia (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
Tanah Bumbu students are spread across several areas of South Kalimantan to continue their studies at university. In this case, the Tanah Bumbu Regional Government provides student housing facilities to students in the Tanah Bumbu area in the form of student dormitories. One of the Tanah Bumbu student dormitories is in Banjarbaru City, South Kalimantan. However, the available dormitory facilities do not meet the standards according to the function of student housing. Student dormitories as student housing have the function of a place to live (residential function), a place to study (educational function) and a place to socialize (social function). Through an architectural program method approach and a multifunctional concept, the zoning of the student dormitory site and space produces a design that not only accommodates residential functions, but is also able to accommodate educational and social functions in accordance with student residential function standards.